Integrated Evaluation of Obesity and Smoking as Synergistic Risk Factors for Cardiovascular Complications. A Cross-Sectional Study - Javed Khurshed Shaikh, Tahir Hussain Soomro, Muhammad Hassan Butt, Muhammad Ismail, Zuhaib Zahoor Soomro, Muhammad Hashim Kalwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Obesity and smoking are independently established risk factors for cardiovascular disease (CVD). However, the combined effect of these two variables as synergistic contributors to cardiovascular complications has not been adequately explored in the Pakistani population. Study Design: The aims of study were to assess the integrated impact of obesity and smoking on cardiovascular risk using a cross-sectional clinical design. Objective: The objectives were to evaluate the synergistic relationship between obesity and smoking as compounding risk factors for cardiovascular complications in adult patients. Methodology: A cross-sectional study was conducted at a tertiary care hospital from January to June 2023. A total of 100 adult patients aged 30–65 years with diagnosed or suspected cardiovascular disease were enrolled using purposive sampling. Participants were categorized into four groups: non-obese non-smokers, obese non-smokers, non-obese smokers, and obese smokers. Body mass index (BMI) was calculated using standard WHO criteria, and smoking status was determined through structured interviews. Cardiovascular outcomes, including hypertension, myocardial infarction, and angina, were recorded from clinical records and patient history. Statistical analysis was performed using SPSS version 25 to evaluate the association and interaction effect of obesity and smoking on cardiovascular events. Results: Among the 100 patients, 28% were obese smokers, 25% obese non-smokers, 22% non-obese smokers, and 25% non-obese non-smokers. The highest frequency of cardiovascular complications was observed in obese smokers (78.6%), followed by obese non-smokers (60%), non-obese smokers (54.5%), and non-obese non-smokers (32%). The interaction between obesity and smoking showed a statistically significant synergistic effect on cardiovascular risk (p<0.01). Conclusion: This study highlights a strong synergistic association between obesity and smoking in elevating the risk of cardiovascular complications. Clinical interventions targeting weight reduction and smoking cessation simultaneously may yield significant cardiovascular health benefits. Keywords: Obesity, Smoking, Cardiovascular Complications, Synergistic Risk.